Faculty of Plantation and Agrotechnology (FPA) seminar - Mohidin, Hasmah; Wilson Ungam, Pryscilla Issah (UiTM Sarawak, 2016)
A talk was successfully delivered by a guest speaker, Dr. Tengoua Fabien Fonguimgo from Cameroon, Central South Africa, during an academic seminar organized by FPA lecturers led by Pn Hasmah Mohidin and Agrovarsity committee members. It was held on 16th October 2015 at Lecture Hall 3, Block M, UiTM Samarahan 1 Campus. The guest speaker, an experienced senior researcher from the Institute of Agriculture Research for Development (IRAD) in Cameroon, gave an enriching talk on "Challenges in Oil Palm Pest and Disease Management" to 248 students of Bachelor in Science (Hons) Technology and Plantation Management and 20 FPA lecturers and Farm Unit staff.